El ἦϑος como vía de acceso a la φύσις La “revolución copernicana” de Platón (Iter, 2022)
This article intends to demonstrate the way Plato’s position regardingthe relation between φύσις and ἦϑος, as well as the role of ἰδέαι in it, constitutes arevolution of the sense in which that relation had beed conceived until then. The firstthree sections present some passages of Heraclitus and Parmenides regarding ἦϑοςand justice (δίκη), with the help of some poetic texts. This results in an outline of the archaic notion of ἦϑος and φύσις, according to which justice constitute an orderingof the κόσμος as a whole. The two following sections show the main characteristicsof Plato’s ἰδέαι, emphasizing the ἰδέα of Good and the importance of the notion ofδύναμις. From this standpoint the foundation of the πόλις proposed in the Republicis presented, in order to observe the passage from a cosmic justice to a notion thatconsiders it as a guiding principle for beings that act according to their ἦϑος and as ameasure that transcends all being, given that it is an ἰδέα.
Keywords: Ancient Greek Philosophy - Heraclitus - History of Ethics - Parmenides - Plato